Translation Lexicon of Traditional Plants as Rice Substitute in Nganjuk Regency, East Java (e-Journal of Linguistics, 2023)
Nganjuk Regency, located in East Java, is known as an agriculturalproduction area. In the past, rice was an expensive food commodity,leading the community to seek rice substitutes. One of the alternativeswas the utilization of various traditional plant lexicons such as tales,gembili, uwi, garut, ganyong, gadung, suweg, and kentang ireng. Theutilization of these plant lexicons by the Nganjuk community reflectstheir close connection with nature. This study aims to provide adescriptive and qualitative depiction of the usage of rice substitutelexicons in the culture of Nganjuk society. Research data was collectedthrough interviews and observations. Interviews were conducted tounderstand the functions and meanings of using rice substitute lexiconsin Nganjuk society.The findings of this study provide a deepunderstanding of the diversity of traditional plant lexicons used as ricesubstitutes in Nganjuk Regency. It was found that mbote / kimpul,gembili, uwi, garut, ganyong, gadung, suweg, and kentang ireng areplants that have long been known and utilized by the Nganjukcommunity as valuable sources of carbohydrates. The utilization ofthese lexicons is not limited to the past but continues to the present.Thecommunity's connection with nature is reflected in their knowledge ofthese plant lexicons. The Nganjuk community has a profoundunderstanding of the benefits and uses of each plant. They appreciatebiodiversity and integrate this knowledge into their daily lives.However, this research also reveals a shift occurring in the youngergeneration. In the modern era, with abundant availability and thedominance of rice consumption, these traditional plant lexicons tend tobe forgotten and less known by the current generation. This highlightsthe need to preserve the knowledge and traditional practices related toplant lexicons as rice substitutes. In this context, this research makes asignificant contribution to enriching the understanding of culturalwealth and traditional values related to food in Nganjuk Regency.These findings can serve as a basis for developing efforts inpreservation, education, and promotion of the use of traditional plantlexicons as healthy and sustainable rice substitutes.
Keywords: traditional plant lexicons; rice substitutes; Nganjuk Regency; biodiversity; local wisdom.